Model Pendampingan UMKM Pangan Melalui Inkubator Bisnis Perguruan Tinggi - Rokhani Hasbullah; Memen Surahman; Ahmad Yani; Deva Primadia Almada; Elisa Nur Faizaty (Institut Pertanian Bogor, 2014)
Business incubator in Indonesia has not developed yet as in developed countries. It is caused by a lack of support from the government and the lack of a model of the concept of business incubation as a reference. This study aimed to develop a mentoring model for food processing SMEs through the Business Incubator in higher education. Research was conducted at several Business Incubators belong to universities by interviewing managers and tenants of the business incubators that have focus on the food processing sector. Data were analyzed using Analytical Hierarchy Process (AHP) and SWOT. The results showed that the most effective incubation models for the food processing SMEs is a model of mentoring participatory. SMEs tenants should be involved in any decision-making process and are actively involved in discussions about their business problems and solutions to overcome their problems. Incubation of tenants is carried out for three years covering the stage of pre incubation, incubation and post-incubation. The main program of incubation for SMEs include technical and managerial training, simple accounting, preparation of business plan, facilitating access to capital and marketing.